PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS TEACHER HERE UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI LIMBAH DI KELAS X AKL SMKN 1 BANAWA - Ratnawaty Ratnawaty (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to determine the increase in science learning outcomes on waste material in Class X AKL SMKN 1 Banawa by applying the Everyone is a Teacher Here strategy in the learning process. This research is a Classroom Action Research using a qualitative descriptive research approach that aims to improve science learning outcomes on waste material in class X AKL SMKN 1 Banawa in the even semester of the 2019/2020 academic year with 12 students as research subjects. Based on the research, it was found that the use of the Active Learning Strategy of Everyone is Teacher Here can increase the activity and results of the waste material science of X AKL students at SMKN 1 Banawa, Donggala district. The active learning strategy of Everyone is Teacher Here has an effect on the following matters. (1) Increase the activity, creativity, and enthusiasm of students so that learning outcomes can increase; (2) Increase time effectiveness, so that less time is wasted; (3) In the learning process, students feel happy and motivated.Everyone Is Teacher Here Learning Strategy, Science Learning Outcomes, Waste